Les agglomérations / vici / castra du Centre-Est de la Gaule : morphologie et fonctions (iiie-viie s. apr. J.-C.) - Michel Kasprzyk (Gallia)
This paper describes a few towns of Central-Eastern Gaul where archaeological, literary, epigraphic, numismatic sources allow to detect the evolution of occupations from the early Empire and how new models appear along the 4th-6th c. AD. It focuses especially on Alise-Sainte-Reine/Alesia, Chalon/Cabillonum, Mâcon/Matisco and Nuits-Saint-Georges in the Aedui civitas; of Saint-More/Cora among the Aedui then in the civitas of Auxerre; of Vertault and Vix in the Lingones civitas. The evolution of the urban topography, public buildings and private architecture is discussed, as well as the nature of economic activities and the eventual place of the public power between the 3rd and 7th c. AD.